Carbon dioxide absorption into promoted potassium carbonate solutions: A review. (October 2016) - Hu, Guoping; Nicholas, Nathan J.; Smith, Kathryn H.; Mumford, Kathryn A.; Kentish, Sandra E.; Stevens, Geoffrey W.
Highlights: Promoters for CO2 hydration in potassium carbonate solutions are reviewed. Promotion mechanisms are summarized. Potential promoters are remarked. Abstract: The emission of carbon dioxide into the atmosphere is recognized as a significant driver for climate change. Carbon capture and storage (CCS) techniques are efficient and effective ways to reduce these emissions to the atmosphere. However, the cost of any carbon capture technique has to be reduced to manageable levels before it can be deployed at an industrial scale. Several methods for capturing carbon dioxide, such as absorption, adsorption, membrane techniques and cryogenic separation have been proposed, of which absorption is the closest to commercial reality. Potassium carbonate is a good solvent for carbon dioxide capture because of its low regeneration energy, low degradation rates and low corrosivity. However, one shortcoming of potassium carbonate in CO2 absorption is that it has relatively slow reaction kinetics with CO2 resulting in the need for large absorption equipment. The most efficient method for improving the absorption kinetics is to add promoters into the potassium carbonate solutions. There have been a number of promoters studied over the last decades, including inorganic promoters such as arsenate, boric acid and vanadate, organic promoters such as different amines and amino acids, enzymatic promoters such as carbonic anhydrase and metal compounds mimicking carbonic anhydrase. In this paper, different promoters for CO2 absorption in potassium carbonate solutions are reviewed and their performance summarized. Additionally, a CO2 hydration promoting mechanism of deprotonation, followed by intermediate formation and then promoter regeneration is presented.